Endomembrane Tension and Trafficking - Saric, Amra; Freeman, Spencer A. (Frontiers in Cell and Developmental Biology, 2021)
Eukaryotic cells employ diverse uptake mechanisms depending on their specialized functions. While such mechanisms vary widely in their defining criteria: scale, molecular machinery utilized, cargo selection and cargo destination, to name a few, they all result in the internalization of extracellular solutes and fluid into membrane-bound endosomes. Upon scission from the plasma membrane, this compartment is immediately subjected to extensive remodeling which involves tubulation and vesiculation/budding of the limiting endomembrane. This is followed by a maturation process involving concomitant retrograde transport by microtubule-based motors and graded fusion with late endosomes and lysosomes, organelles that support the degradation of the internalized content. Here we review an important determinant for sorting and trafficking in early endosomes and in lysosomes; the control of tension on the endomembrane. Remodeling of endomembranes is opposed by high (hydrostatic) tension and supported by the relief of tension. We describe how the timely and coordinated efflux of major solutes along the endocytic pathway affords the cell control over such tension. The channels and transporters that expel the smallest components of the ingested medium from the early endocytic fluid are described in detail as these systems are thought to enable endomembrane deformation by curvature-sensing/generating coat proteins. We also review similar considerations for the lysosome where resident hydrolases liberate building blocks from luminal macromolecules and transporters flux these organic solutes to orchestrate trafficking events. How the cell directs organellar trafficking based on the luminal contents of organelles of the endocytic pathway is not well-understood, however, we propose that the control over membrane tension by solute transport constitutes one means for this to ensue.